2013
DOI: 10.1089/cell.2012.0042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Donor Fibroblast Cell Type and Transferred Cloned Embryo Number on the Efficiency of Pig Cloning

Abstract: Currently, cloning efficiency in pigs is very low. Donor cell type and number of cloned embryos transferred to an individual surrogate are two major factors that affect the successful rate of somatic cell nuclear transfer (SCNT) in pigs. This study aimed to compare the influence of different donor fibroblast cell types and different transferred embryo numbers on recipients' pregnancy rate and delivery rate, the average number of total clones born, clones born alive and clones born healthy per litter, and the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Our result showed that the cloning efficiency associated with MSCs (0.9%) is significantly higher than that resulting from using Fs as donor cells for cloning (0%). Moreover, our study showed that all the cloned piglets derived from MSCs were born alive and did not exhibit any visible defects, which usually could be seen in piglets cloned from Fs (Li et al, 2013;Schmidt et al, 2010). This strongly suggests that MSCs can serve as suitable donor cells that could be more efficiently reprogrammed to produce cloned pigs through SCNT, as compared with fibroblasts.…”
Section: Figsupporting
confidence: 50%
See 3 more Smart Citations
“…Our result showed that the cloning efficiency associated with MSCs (0.9%) is significantly higher than that resulting from using Fs as donor cells for cloning (0%). Moreover, our study showed that all the cloned piglets derived from MSCs were born alive and did not exhibit any visible defects, which usually could be seen in piglets cloned from Fs (Li et al, 2013;Schmidt et al, 2010). This strongly suggests that MSCs can serve as suitable donor cells that could be more efficiently reprogrammed to produce cloned pigs through SCNT, as compared with fibroblasts.…”
Section: Figsupporting
confidence: 50%
“…The SCNT experiments for both fibroblasts and MSCs were performed under the same conditions and following the protocol described by us (Li et al, 2013). Briefly, each batch of & 500-600 matured porcine oocytes was randomly separated into two equal portions; one portion was used for SCNT with fibroblasts and the other portion was used for SCNT with the same donor pig's MSCs.…”
Section: Somatic Cell Nuclear Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we also investigated whether differences in these cell populations exist between pEFs derived from different pig breeds, as recent research revealed that pEFs from different breeds affected somatic cell nuclear transfer efficiency. 24 In this case, it was shown that pEFs derived from the Chinese Laiwu pig resulted in significantly improved reprogramming compared with pEFs derived from other pig breeds.…”
Section: Introductionmentioning
confidence: 87%